Early or Delayed Reversal of Temporary Ileostomy after Typhoid Perforation: A Comparative Study at Tertiary Care Hospital - Shaikh, Shiraz; Laghari, Zameer Hussain; Laghari, Qamber Ali; Abro, Shahnawaz; Dal, Nawaz Ali (Journal of Liaquat University of Medical & Health Sciences, 2020)
Objective: To compare the effectiveness of early reversal versus delayed reversal of temporary ileostomy after typhoid perforation in terms of morbidity and mortality at Liaquat University of Medical and Health Sciences. Methodology: This prospective comparative study was conducted in department of surgery, Liaquat University of Medical and Health Sciences, Jamshoro from April 2018 to March 2019. Patients admitted in the surgical unit, underwent temporary ileostomy after typhoid perforation either of gender were enrolled. Patients were equally divided in two groups via lottery method. Patients of group I underwent early reversal of temporary ileostomy and patients of group II underwent delayed reversal of temporary ileostomy. Effectiveness was assessed in terms of postoperative complication and mortality including hospital stay. Data was collected through self-made proforma and analyzed by SPSS version 20. Results: Total 78 patients were enrolled and their mean age was 28.2±10.3 years of early reversal group and 33.5±6.3 of group late reversal group. Males were most common in both groups i.e. 67.0% in group I and 64.0% in group II. According to the postoperative complications; skin excoriation, parastomal hernia, wound infection and intra-abdominal collection were insignificant among both groups. Prolonged hospital stay was higher in patients of late reversal group as compared to early reversal group, p-value 0.004. Conclusion: It was concluded that early reversal of temporary ileostomy is feasible and safe, though by early reversal of temporary would yield economic and administrative benefits to the department and personal benefits for patients to live a better quality of life much earlier.